A Comparison of Using Multiple Choice and Cloze Tests on Students’ Achievement in Reading Comprehension at Second Semester of English Department of FKIP Batanghari University - Silfia, Efa (Universitas Batanghari Jambi, 2024)
The purpose of the study was to find out the comparative achievement of multiple choice test and bracket test in reading comprehension in the second semester of the department of english, University of FKIP Batanghari. This study used a mixed method approach. The subject of the test would be second semester english students of FKIP Batanghari University. Data was collected through two instruments, which were a test and an interview. Based on the results of this study, the author found that students scored higher in the cloze test than in the multiple choice test. The result of the interview showed that the students preferred to answer the question in the cloze test than in the multiple choice question because they were easier to understand. These perceptions confirm the differences in student scores on the first research question. However, the result also showed that the multiple choice test is a better measure of students' reading comprehension. The students' impressions and opinions about the tests and their own performance were recorded and considered. Implications of results and recommendations further research is needed to obtain detailed and usable information to improve students' reading comprehension and achievement in the future.